Karakteristik Amilografi Tepung Jagung Termodifikasi dengan Fermentasi Spontan dan Perendaman dalam Larutan Kalsium Hidroksida - Tjahja Muhandri; Papang Sulton Nularif; Dase Hunaefi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
The research was aimed to study the effect of spontaneous fermentation and soaking in 1% (w/v) calcium hydroxide (Ca(OH)2) of the corn grits (cultivar varieties of P21) on the yield of corn flour and its pasting properties. Spontaneous fermentation with the ratio water to grits of 3 : 1 was conducted in a closed container for 12, 24, 48, and 72 hours, while the soaking treatment in a solution of 1% (w/v) Ca(OH)2 was performed for 1, 2, and 3 hours with the ratio solution to the grits of 2:1. The results showed that spontaneous fermentation and soaking in a solution of Ca(OH)2 of corn grits increased the yield and peak viscosity of corn flour. Those treatments also decreased the initial gelatinization tempe-rature, maximum gelatinization temperature, viscosity breakdown and retrogradation of the corn flour.